The Effect of Combining Astaxanthin and Vitamin E on IL-1, IL-6, And CRP Levels - Sampurna Sampurna; Rita Kartika Sari; Mutiara Hanif Syafitri; Nafla Aqilah; Saskia Febrian Dwi (Indonesian Journal of Global Health Research, 2026)
Carrageenan-induced inflammation binds to TLR-4, activating the NF-kβ pathway, which attracts macrophages to release proinflammatory cytokines, Interleukin-1 and Interleukin-6, leading to the production of CRP. Astaxanthin and vitamin E have anti-inflammatory effects, but their combined effects are poorly studied. This study examines whether astaxanthin combined with vitamin E reduces IL-6, IL-1, and CRP levels in male Wistar rats induced by carrageenan. This experiment used a post-test-only control-group design with groups: KN (standard feed), KS (1% carrageenan induction), and KP (combination of 0.72 mg/kgBW astaxanthin and 24.1 mg/kgBW vitamin E). ELISA was performed 24 hours after carrageenan induction. Parametric data analysis was performed, followed by a post hoc test. The results showed that IL-1 levels were highest in KS (1.61 pg/mL), followed by KP (0.42 pg/mL) and KN (0.28 pg/mL). Statistical analysis (one-way ANOVA and post hoc tests) identified significant differences among all groups (p<0.05). IL-6 levels decreased in KP (58.67 pg/mL) compared to KS (98.83 pg/mL). CRP levels were highest in KS (2.35 ng/mL), followed by KP (1.01 ng/mL) and KN (0.75 ng/mL), with KS showing a significant increase compared to KN (p<0.05). From these results, it can be concluded that the combination of astaxanthin and vitamin E has an anti-inflammatory effect on IL-6, IL-1, and CRP levels in male Wistar rats induced by carrageenan.